Nonlinear modeling of saguaro growth rates reveals the importance of temperature for size‐dependent growth. Issue 10 (17th September 2019) - Félix‐Burruel, Ricardo E.; Larios, Eugenio; Bustamante, Enriquena; Búrquez, Alberto
Abstract : Premise: The saguaro cactus is an iconic species of the Sonoran Desert. Its individual growth rates have been investigated for over 100 years. Its growth dynamics have been studied using phenomenological models intended to estimate growth, but not to understand the underlying biological processes. Most studies have suggested summer rainfall as the sole factor determining saguaro growth, overlooking the influence of other factors related to the process of growth. Methods: We analyzed the annual growth rates for 13 saguaro populations in the Sonoran Desert using nonlinear models. These are better suited to analyze growth since they consider the fact that maximum growth rates diminish just before the onset of reproduction. We related model parameters to the local climate. Results: The most parsimonious model was the Ricker function that described growth considering cactus decline with age. Variance in temperature, rather than precipitation, was more closely related to growth. Higher variance in temperature at the beginning of the warm season was detrimental to saguaro growth. Conclusions: Simple nonlinear equations modeled growth rate using biologically interpretable parameters related to climate factors. Because the temperature is projected to increase in both mean and variance by climate change, the population dynamics of this iconic cactus are likely to be affected.